DECISION SUPPORT SYSTEM TO DETERMINE SCHOLARSHIP RECIPIENTS AT SMAN 1 BANGUNREJO USING SAW METHOD - Tri Susilowati; Suyono Suyono; Widi Andewi (STMIK Pringsewu Lampung, 2017)
SMAN 1 Bangunrejo is still a lot of parents who belong to underprivileged families economy, therefore the programs that support the smooth prosses learning as highly desirable for smooth scholarship students in completing education. Distribution of scholarships is done by the Department of Education Central Lampung greatly assist students who are not able to or achievement during their studies. To assist the determination in determining the eligible student then takes a decision support system. In the process of development of a decision support system to determine the scholarship recipients at SMAN 1 Bangunrejo use traditional methods Simple Additive Weighting (SAW). This method was chosen because it is able the best alternative from a number of alternatives, in this case the alternative meant that the right to receive scholarships based on criteria specified. Research done by finding the weight values for each attribute, then do ranking process that will determine the optimal alternative, that the best students achieving the eligible. Based on test results, a system built to help the working team selectors scholarship, can accelerate the scholarship selection process, can reduce errors in determining the scholarship recipients, so the scholarships granted in accordance with the target.